(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Contribution of Female Chili Farmers in Increasing Household Income (Case Study in Sidemen district, Karangasem Regency. The study aims to analyze the contribution of female chili farm workers to household income and to analyze the factors that influence the size of the income of female chili farm workers. The primary data used was obtained through interviews and observations conducted to women chili farm workers sidemen subdistrict, Karangasem regency as many as 30 people. Secondary data is obtained from journals, previous research and internet data. The data analysis techniques used in this research are qualitative and quantitative analysis techniques with multiple linear regression analysis. The dependent variable (Y) is the contribution of female chili farm workers and the independent variable (X) is the husband’s income, the number of household dependents and work experience. The results showed that the contribution of women chili farm workers in increasing household income in Sidemen Subdistrict was 45.36%. The total household income of women farm workers for six months is Rp. 786,210,000 or Rp 4,367,833 per month with an average number of household members as many as three people so that the household income of women farm workers exceeds the monthly income of Karangasem Regency by Rp.1,445,944, therefore the condition of women farm laborers in Sidemen District is included in the category of sufficiency. The results of the analysis explained that the income factor of the husband has a negative and significant influence on the contribution of women’s income chili farm workers, the number of household dependents has a positive and significant influence on the contribution of women as farm workers, while the experience of working has no real effect on the contribution of women chili farm workers.